IMPLEMENTASI METODE WEIGTHED PRODUCT PADA SISTEM PENDUKUNG KEPUTUSAN UNTUK PENILAIAN KINERJA KARYAWAN PT. JAMKRIDA - Nova Noor Kamala Sari (Universitas Palangka Raya, 2020)
The application of information technology in the field of Human Resource Management greatly facilitates the work of administrative issues in relation to Human Resource. The use of information technology in the processes requires well-trained human resources. As a company that has several units, the Human Resources who work at PT. JAMKRIDA are expected to have good performance to support the company's progress. Therefore, a performance evaluation system is needed. Decision support system used the Weighted product method to complete the calculation. Software development methodology applied waterfall starting from the requitments definition, system and software design to the implementation phase made by PHP and MyAdmin database, and black box testing. It is concluded that decision support system for evaluating the employee’s performances does assessment by using criteria and items of assessments referring to PT. Jamkrida. Assessments are carried out online so it is expected to replace the manual old system.